2019
DOI: 10.3390/coatings9050327
|View full text |Cite
|
Sign up to set email alerts
|

Icariin-Functionalized Coating on TiO2 Nanotubes Surface to Improve Osteoblast Activity In Vitro and Osteogenesis Ability In Vivo

Abstract: Surface modification of titanium is encouraged to facilitate early osseointegration in dental and orthopedic fields. Icariin is the main active constituents of Herba Epimedii, which has good bone-promoting ability. We established an icariin-functionalized coating composed of icariin and poly (lactic-co-glycolic acid) (PLGA) on TiO2 nanotubes surface (NT-ICA-PLGA) to promote osteoblast cell activity and early osseointegration. Surface topography, wettability and drug release pattern of the established NT-ICA-PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Moreover, the 15VZn and 25VZn groups revealed obviously higher osteogenic gene expressions than the other groups, with the highest ALP, OPN and Runx-2 gene expressions in the 15VZn group and the highest levels of COL1a1 gene expression in the 25VZn group. These results suggested that, similar to previous reports, 3,11,24 the TNT structure could increase osteogenic gene expression. More importantly, the addition of Zn on the TNT surface could gain additional osteogenic effect, with the 15VZn group displaying substantially superior osteogenic effect compared with the other Zn-loaded groups.…”
Section: Osteogenic-related Gene Expressionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, the 15VZn and 25VZn groups revealed obviously higher osteogenic gene expressions than the other groups, with the highest ALP, OPN and Runx-2 gene expressions in the 15VZn group and the highest levels of COL1a1 gene expression in the 25VZn group. These results suggested that, similar to previous reports, 3,11,24 the TNT structure could increase osteogenic gene expression. More importantly, the addition of Zn on the TNT surface could gain additional osteogenic effect, with the 15VZn group displaying substantially superior osteogenic effect compared with the other Zn-loaded groups.…”
Section: Osteogenic-related Gene Expressionsupporting
confidence: 91%
“…By comparison with the two alternative methods mentioned above, conditioned medium co-culture was chosen in this experiment to assess OIM because of its simple, rapid procedure and good testing repeatability. 77 Since MC3T3-E1 cells are widely used as cell model systems in bone biology, 3 we employed this cell line to evaluate the OIM capabilities of different biomaterials in this experiment.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, icariin is also a promising osteoinductive compound for bone tissue engineering [11,16]. We previously reported that the icariin-functionalized coating on TiO 2 nanotubes surface promote osteoblast function and accelerate osseointegration [17]. Moreover, recently the anti-inflammatory [18,19] and immunoregulatory [20] functions of ICA has also been raised.…”
Section: Introductionmentioning
confidence: 99%